2015
DOI: 10.4238/2015.july.14.8
|View full text |Cite
|
Sign up to set email alerts
|

An expression profiling analysis of hybrid millet and its parents at grain filling stage

Abstract: ABSTRACT. Heterosis has been widely used in crop breeding and production. However, a shortage of genes known to function in heterosis significantly limits our understanding of the molecular basis underlying heterosis. Here, we report 740 differentially expressed genes (DEGs) in the leaves of the hybrid millet Zhang No.5 and its parents at the grain filling stage determined using Solexa Illumina digital gene expression. Of the 740 DEGs, 546 were from the hybrid and its parents and most were up-regulated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…As a hybrid millet, it has expressed heterosis in terms of genes and yield. A study that identified 740 differentially expressed genes between hybrid millet and its parent lines found that most of these genes were upregulated in the hybrid [3]. Increased yield of Zhang hybrid millet has been reported every year, and it has already reached more than 400 kg yield per thousand hectares in 2011.…”
Section: Introductionmentioning
confidence: 99%
“…As a hybrid millet, it has expressed heterosis in terms of genes and yield. A study that identified 740 differentially expressed genes between hybrid millet and its parent lines found that most of these genes were upregulated in the hybrid [3]. Increased yield of Zhang hybrid millet has been reported every year, and it has already reached more than 400 kg yield per thousand hectares in 2011.…”
Section: Introductionmentioning
confidence: 99%